How to Dax? Preschool Children’s Prosocial Behavior, But Not Their Social Norm Enforcement Relates to Their Peer Status - Paulus, Markus (Frontiers in Psychology, 2017)
The current study examined correlates of preschool children’s (n=82) peer status. In particular, we assessed children’s prosocial behavior, social problem behavior, norm enforcement, language abilities, and temperament. Children’s prosocial behavior, pragmatic language abilities, and gender correlated with peer status. A regression analysis revealed that prosocial behavior and gender were independent predictors. There was some evidence for a mediation effect: The link between pragmatic language and peer status was mediated by prosocial behavior. Children’s norm enforcement was not related to peer status, neither was it related to any other factor such as temperament or language. Overall, the study supports approaches claiming that prosocial behavior plays a role in children’s social functioning and are in line with social-interactionist accounts to social and social-cognitive development.